A study on the effects of Kalman Filter on performance of IPMC-Based Active Vibration Control Scheme - Bandopadhya, Dibakar; Njuguna, James A. K. (Institute of Electrical and Electronics Engineers (IEEE), 2010)
This paper evaluates the effectiveness and performance of Ionic Polymer Metal Composite (IPMC) based active vibration control scheme equipped with the Kalman estimation algorithm. To assess the vibration attenuation efficiency, a rotating flexible manipulator has been modelled integrating two IPMC actuators following the modal approach. The elastic displacements as generalized coordinates for estimating optimal performance is carried out next by discretizing the elastic motion through the assumed mode technique and applying the Kalman filter. Simulations are then performed to demonstrate effective vibration attenuation using both IPMC and the Kalman filter. Kalman filter is employed for the whole vibrating system taking into account of the bending moment generated by the IPMC actuator. Experiment is conducted for the proposed damping scheme and the results are compared and verified with the simulation results.
Keywords: Active vibration control; electro-active polymer (EAP); heaviside function; ionic polymer metal composite (IPMC)